# How many ounces are equal to 1 1/2 pounds

## Answers

24, 16 ounces is 1 pound. Half is 8 16+8=24

The answer is 12 fluid ounces

112 ounces are in 7 pounds

Step-by-step explanation:

because there are 16 ounces in 1 pound if you multiply 16 by 7 you will get 112 oz.

112

Step-by-step explanation:

16 ounce multiply that by 7. 112. This correct i googed it

112

Step-by-step explanation:

multiply the mass value by 16

48 ounces

Step-by-step explanation:

16 ounces per pound

3 x 16 = 48 ounces

7 Pounds Equals 112.0000oz.

Have A Great Day!

we have that

1 pound (lb) = 453.6 grams

1 pound (lb) = 16 ounces (oz)

so

453.6 grams = 16 ounces (oz)

453.6 grams-------> convert to Kg-----> 453.6/100=0.4536 Kg

0.4536 Kg = 16 ounces (oz)

we know that

Zeroes at the end of numbers containing a decimal point are considered to be significant,

so

the number 0.0003140 kg ------> has 4 significant figures

by proportion

[tex]\frac{16}{0.4536} \frac{oz}{kg} = \frac{x}{0.0003140} \frac{oz}{kg} \\ \\0.0003140*16=0.4536*x \\\\ x= \frac{0.0003140*16}{0.4536} \\\\ x= 0.01108\ ounces[/tex]

[tex]x= 0.01108= 1.108*10^{-2} \ oz[/tex] ----> this number has 4 significant figures

therefore

the answer is

[tex]1.108*10^{-2} \ oz[/tex]

Why did you7 ask a question then anwser it yourself

Step-by-step explanation:

Hk its the Third One

costs the what? what is the cost of the pants?

step-by-step explanation:

if it is $10, then the price is 14.

take 40% of the cost, and then add the cost.

40% of 10 = 4

4+10 = 14.

answer:

given the linear inequality : [tex]x-2y\geq -12[/tex]

add 2y to both sides we get;

[tex]x-2y+2y\geq -12+2y[/tex]

simplify:

[tex]x\geq -12+2y[/tex]

add 12 to both sides of an equation;

[tex]x+12\geq -12+2y+12[/tex]

simplify:

[tex]x+12\geq 2y[/tex]

divide both sides by 2 we get;

[tex]\frac{x}{2} + 6 \geq y[/tex]

or

[tex]y\leq \frac{x}{2} + 6[/tex]

the related equation for the inequality equation [1] is;

[tex]y =\frac{x}{2} +6[/tex]

y-intercepts defined as the graph crosses the y-axis.

substitute x =0 in [2] to solve for y;

[tex]y =\frac{0}{2} +6[/tex]

y = 6

x-intercepts defined as the graph crosses the x-axis.

substitute value y = 0 to solve for x;

[tex]0 =\frac{x}{2} +6[/tex]

subtract 6 from both sides we get

[tex]0-6 =\frac{x}{2} +6-6[/tex]

[tex]-6 =\frac{x}{2}[/tex]

multiply both sides by 2 we get;

[tex]-6 \times 2=x[/tex]

or

x = -12

now, plot these point (0, 6) and (-12, 0) on graph as shown below and shade the graph below the solid line.